2017
DOI: 10.1002/cpt.682
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacology and Therapeutics Education in the European Union Needs Harmonization and Modernization: A Cross‐sectional Survey Among 185 Medical Schools in 27 Countries

Abstract: Effective teaching in pharmacology and clinical pharmacology and therapeutics (CPT) is necessary to make medical students competent prescribers. However, the current structure, delivery, and assessment of CPT education in the European Union (EU) is unknown. We sent an online questionnaire to teachers with overall responsibility for CPT education in EU medical schools. Questions focused on undergraduate teaching and assessment of CPT, and students' preparedness for prescribing. In all, 185 medical schools (64%)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
85
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(93 citation statements)
references
References 23 publications
2
85
0
4
Order By: Relevance
“…Indeed, recent studies have reported that CPT education is still based mainly on traditional learning methods (e.g. lectures and oral exams) 11, and is often not taught and assessed separately because the subject is integrated into broader course designs 62.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, recent studies have reported that CPT education is still based mainly on traditional learning methods (e.g. lectures and oral exams) 11, and is often not taught and assessed separately because the subject is integrated into broader course designs 62.…”
Section: Discussionmentioning
confidence: 99%
“…To improve CPT education in undergraduate European medical curricula, we recently formulated a list of recommendations that could also be useful elsewhere (e.g. the USA) 11. More emphasis should be given to training medical students in clinical practice, preferably as early as possible during medical training, with students being responsible for patient care under the supervision of a senior clinician 96.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A report by Maxwell and Webb in 2006 also documented the disappearance of dedicated courses and assessments related to CPT in the UK, which in turn decreased the available time devoted to improving prescribing competence . The European Association of Clinical Pharmacology and Therapeutics has also reported a need to restructure their current CP education to deal with deficiencies in CP knowledge and practical prescribing skills …”
Section: Introductionmentioning
confidence: 99%
“…10 The European Association of Clinical Pharmacology and Therapeutics has also reported a need to restructure their current CP education to deal with deficiencies in CP knowledge and practical prescribing skills. 11 In the UK, the mandatory Prescribing Safety Assessment was developed by the Medical Schools Council and British Pharmacological Society to ensure that graduating medical students met a threshold of CP knowledge and prescribing skills. However, British students had previously noted that there were insufficient opportunities to learn about medications during medical school potentially making it difficult to meet the expectations of the Prescribing Safety Assessment.…”
Section: Introductionmentioning
confidence: 99%